2010
DOI: 10.22456/2177-0018.17615
|View full text |Cite
|
Sign up to set email alerts
|

Participação das mulheres na graduação da Faculdade de Odontologia da Universidade Federal do Rio Grande do Sul

Abstract: Introduction: In 1866, in the University of Ohio graduated the first woman in the history of Dentistry, The inclusion of women in dentistry has occurred slowly and gradually, following the historical and cultural development of society. One factor that makes women choose the dental career is being able to perform the work autonomously. Objective: Knowing the growth of women's participation in the Faculty of Dentistry, Federal University of Rio Grande do Sul (UFRGS-FO). Materials and Methods: The documents that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0
20

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 2 publications
1
3
0
20
Order By: Relevance
“…The present study showed predominance of women in the student sample, following a gradual increase of females in health area courses over the years (Baldissera et al, 2010), and it is known that this predominance is also present in the Brazilian population (IBGE, 2011). This gender feature in medical, nursing, physiotherapy and pharmacy schools is a finding that agrees with data obtained from the National Survey of Student Performance in 2013 (INEPEAT 2013a, INEPEAT 2013b, INEPEAT 2013c, INEPEAT 2013d, although some specific studies can differ, as in the cross-sectional study with 370 medical students conducted in Pernambuco in 2006 and 2007, which found percentage of 57.0% of females (Alves et al, 2010).…”
Section: Discussionsupporting
confidence: 59%
“…The present study showed predominance of women in the student sample, following a gradual increase of females in health area courses over the years (Baldissera et al, 2010), and it is known that this predominance is also present in the Brazilian population (IBGE, 2011). This gender feature in medical, nursing, physiotherapy and pharmacy schools is a finding that agrees with data obtained from the National Survey of Student Performance in 2013 (INEPEAT 2013a, INEPEAT 2013b, INEPEAT 2013c, INEPEAT 2013d, although some specific studies can differ, as in the cross-sectional study with 370 medical students conducted in Pernambuco in 2006 and 2007, which found percentage of 57.0% of females (Alves et al, 2010).…”
Section: Discussionsupporting
confidence: 59%
“…In Brazil, there has been a considerable increase in the presence of women in healthcare professions. This increase took place after the 1970s, and is partly justified by feminist movements, by changes in cultural standards and in the values of the social role of women in society (Baldissera et al, 2010;Costa et al, 2010). One of the factors that helps make women opt for a dental career is the possibility of exercising the profession autonomously, allowing her to exercise the profession and take care of the family (Baldissera et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…This increase took place after the 1970s, and is partly justified by feminist movements, by changes in cultural standards and in the values of the social role of women in society (Baldissera et al, 2010;Costa et al, 2010). One of the factors that helps make women opt for a dental career is the possibility of exercising the profession autonomously, allowing her to exercise the profession and take care of the family (Baldissera et al, 2010). Thus, in Brazil, as in other countries, the number of students entering courses in the health area, including Dentistry, is predominantly female, which may partially explain the results mentioned above.…”
Section: Discussionmentioning
confidence: 99%
“…Os egressos que constituíram a amostra deste estudo totalizaram 172 participantes, formados no período de 2012/1 até 2017/2, com média de 26±1,88 anos de idade e variação de 23 a 35 anos, sendo que a maioria (70,1%) se autodeclararam do sexo feminino (n=117). Desde a década de 70, quando a mulher efetivamente entrou no mercado de trabalho odontológico, até os dias atuais, tem havido um gradual aumento da participação feminina na profissão, culminando com o seu predomínio numérico em relação ao sexo masculino 14 .…”
Section: Caracterização E Inserção Dos Egressosunclassified